The Replacement Of Cyanide By a New Organic Depressant In Seelective Flotation Of Polymetallic Lead-Zinc-Silver Ores - A. V. Glembotsky; V. A. Glinkin; V. P. Seregin; N. A. Greshnova (Society for Mining, Metallurgy & Exploration, 1995)
Based on a new alternative depressant of zinc sulphide - dimethyldithiocarbamate- modern technology has been developed for the treatment of complex polymetallic ores. In addition to its general function (depression of sphalerite and iron sulphides to some extent), this double-acting reagent is a promoter for galena and silver minerals. Laboratory and plant tests, as well as industrial experience have all shown consistently higher silver recovery to the lead concentrate as compared with sodium cyanide, resulting in less pollution and a safer environment